PROFIL KOLESTEROL TOTAL PADA PENDERITA PENYAKIT JANTUNG KORONER DI RUMAH SAKIT UMUM DAERAH KOTA KENDARI - Ani Umar; firdayanti firdayanti; Nur Hijreah Samsu (Program Study of Medical Laboratory Technology , Politeknik Bina Husada Kendari, 2022)
Total Cholesterol profile in patients with coronary heart disease at the city general hospital in kendari”. Coronary heart disease is one of the three main causes of death in the world each years. PJK is a disease that arises due to narrowing or blockage of arteries that enter the bloodstream to the heart muscle so that there is a lack of oxygen supply to the heart muscle. Total cholesterol is the total amount of cholesterol in the blood. Examination of total cholesterol which is a blood test that functions to determine total cholesterol levels in patients with coronary heart disease. The purpose of this study was to determine the total cholesterol profile in patients with coronary heart disease in the general hospital area of the city of kendari with enzymatic kinetic methods. Samples of patients with coronary heart disease as many as 18 samples with sampling techniques namely accidental sampling. Based on the research that has been done obtained results that there are 5 people (27%) have level ≥ 200 mg/dL shows an increase in total cholesterol levels and 13 people (72%) have level ≤ 200 mg/dL showing normal cholesterol levels. Key Words : Coronary Heart Disease, Total Cholesterol, Examination of Total Cholesterol.